2013
DOI: 10.2147/cia.s42700
|View full text |Cite
|
Sign up to set email alerts
|

The ability of NT-proBNP to detect chronic heart failure and predict all-cause mortality is higher in elderly Chinese coronary artery disease patients with chronic kidney disease

Abstract: ObjectiveTo analyze the relationship between N-terminal pro-brain natriuretic peptide (NT-proBNP) and renal function, and compare the ability and cut-off thresholds of NT-proBNP to detect chronic heart failure (CHF) and predict mortality in elderly Chinese coronary artery disease (CAD) patients with and without chronic kidney disease (CKD).MethodsThe study included 999 CAD patients older than 60 years. The endpoint was all-cause mortality over a mean follow-up period of 417 days.ResultsThe median age was 86 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 27 publications
0
13
0
2
Order By: Relevance
“…The pooled risk ratios between patients with preserved and diminished renal function were not significantly different (p-value=0.652), and there was significant heterogeneity in both sub-groups (Figure 2A and 2B). Four of the studies used higher NT-proBNP cut-points for patients with renal dysfunction 28,33-35 , while the remaining studies used the same NT-proBNP cut-points in the different sub-groups of renal function.…”
Section: Resultsmentioning
confidence: 99%
“…The pooled risk ratios between patients with preserved and diminished renal function were not significantly different (p-value=0.652), and there was significant heterogeneity in both sub-groups (Figure 2A and 2B). Four of the studies used higher NT-proBNP cut-points for patients with renal dysfunction 28,33-35 , while the remaining studies used the same NT-proBNP cut-points in the different sub-groups of renal function.…”
Section: Resultsmentioning
confidence: 99%
“…Fu et al [24] reported that NTproBNP predicted death with a cut-off value of 369.5 pg/ml in non-CKD patients and a cut-off value of 2584.1 pg/ml in CKD patients. In the present study, the risks of all-cause death and MACEs were particularly increased in patients with NT-proBNP levels ≥ 411.3 pg/ml, suggesting this value as an appropriate cut-off NT-proBNP level for prediction of all-cause death and MACEs in very old patients with stage 3 CKD.…”
Section: Discussionmentioning
confidence: 99%
“…The association was significantly stronger in those with than without proteinuria (interaction P=0.05) (35). In Chinese patients with known CAD, NT-pro-BNP was associated with all-cause death if eGFR was ,60 ml/min per 1.73 m 2 (36). In addition, the NT-pro-BNP cutoff associated with mortality was higher in patients with CKD (2584 pg/ml) than in persons without CKD (370 pg/ml) (36).…”
Section: Bnp and Hard Outcomes In Ckdmentioning
confidence: 94%
“…In Chinese patients with known CAD, NT-pro-BNP was associated with all-cause death if eGFR was ,60 ml/min per 1.73 m 2 (36). In addition, the NT-pro-BNP cutoff associated with mortality was higher in patients with CKD (2584 pg/ml) than in persons without CKD (370 pg/ml) (36). Several other studies reported similar associations between NT-pro-BNP, CV events, and all-cause death (Table 2) (37-39).…”
Section: Bnp and Hard Outcomes In Ckdmentioning
confidence: 98%